TOWARDS FUTURE OF POLISH TOURISM – A POTENTIAL OF COMPETITIVENESS OF THE TOURIST INDUSTRY - Bednarczyk, Małgorzata (Acta Scientiarum Polonorum. Oeconomia, 2010)
Currently difficult tourist market may be an area of development chances of Polish tourist industry in effect of activity of government administration before and in time of the Polish presidency at the Council of the European Union and natural impulses of innovativeness resulting from a crisis. Taking these chances depends on the potential of competitiveness of the Polish tourist industry from the point of view of its strategic changing ability. In the paper were presented synthetic results of empirically verified monitoring of competitiveness potential of small and medium tourist enterprises conducted for three years on the base of the author’s model. The measurement comprised outer and inner levers of competitiveness of Polish tourist enterprises. A level of inertia gaps of economic autonomies and local administration, and competitiveness gaps of tourist enterprises were assessed.